Pemberian Kedelai Hitam (Glycine soja) Meningkatkan Ekspresi RE-alpha Aorta Tikus Ovariektomi - Yuliawati, Dwi; Astuti, Wuri Widi; Yuniarti, Fitri (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
Menopause is a condition in women characterized by decreased estrogen function due to decreased ovarian function and has an impact on increasing the occurrence of cardiovascular problems. Fulfillment of estrogen needs in menopause can use phytoestrogens from black soybeans. The study aims to prove that black soybean (Glycine soja) can increase RE-? expression in the aorta of ovariectomized rats. Research samples (25 female rats) were randomly divided into 5 groups: negative control group (K-), positive control (K+) and treatment (P1, P2, P3). Ovariectomy was performed on K+ and P1,P2,P3. Thirty days post ovariectomy, the rats were treated with black soybean doses of 50, 100, 150 mg/200 g/day for 30 days. RE-? expression using immunohistochemical method. The results of Kruskal Walls analysis (?=0.05) showed a p value of 0.027 < ?=0.05, meaning that there is a significant effect of black soybean administration on increasing the expression of RE-? in the aorta of ovariectomized rats. Post Hoc testing with Mann Whitney showed a significant increase in RE-? expression in the 150 mg/200 gr/day dose treatment group compared to the positive control group (K+).